After the Brits Have Gone and the Trumpets Have Sounded: Turning a Drama into a Crisis That Will Not Go to Waste - Mark Blyth (Intereconomics, 2016)
The EU institutions must diagnose the crisis that Brexit and Trump have brought to the fore as an economic crisis that is malleable to policy, and they must forcibly sell that diagnosis to the member states if they want to halt the further disintegration of the EU. Doing so would give member states room to experiment with locally appropriate policies rather than simply accept "one size fits none" policy rules. Such a diagnosis would be nothing less than an explicit political intervention by a supposedly technocratic set of institutions. But technocracies work best in good times, and these are not good times.
Keywords: 330